2012
DOI: 10.12973/eu-jer.1.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Knowledge on Secondary School Students’ Scientific Creativity Skills in Nakuru District, Kenya

Abstract: The purpose of this study was to investigate the influence of gender and knowledge on scientific creativity among form three biology students (third year in secondary school cycle) in Nakuru district in Kenya. The cross-sectional survey research was employed. The population of the study comprised all form three biology students in public secondary schools in Nakuru district. A sample of eight schools with a total of 363 students was selected from the population using stratified sampling technique. Two instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…These results are in agreement with the findings of Okere and Ndeke (2012) and Hungi (2009) who found out that the level of scientific creativity in Biology were low and findings of Okere (1986) who found that the level of scientific creativity in Physics were low. Similar findings were reported in a study conducted by Siti (2008) which aimed to measure the level of creativity of students in the science program at the Faculty of Education, Universiti Teknologi Malaysia.…”
Section: Creativity Level In Chemistrysupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with the findings of Okere and Ndeke (2012) and Hungi (2009) who found out that the level of scientific creativity in Biology were low and findings of Okere (1986) who found that the level of scientific creativity in Physics were low. Similar findings were reported in a study conducted by Siti (2008) which aimed to measure the level of creativity of students in the science program at the Faculty of Education, Universiti Teknologi Malaysia.…”
Section: Creativity Level In Chemistrysupporting
confidence: 93%
“…A study in Kenya by Ndeke (2003) found that there was a positive and significant relationship between creativity and gender in Biology. Other studies, Okere & Ndeke (2012), Yuan Z., Wang-Bing S., Chun-Hua S., & Mei-Cun L. (2017) found that scientific creativity performance of male was significantly better than female for post graduate students. In another study by Shin, J., Jung, H., Choe, S. & Han, K. (2002) findings indicated that girls, rather than boys, showed better creative performances, demonstrating moderately higher average scores on the three creative measures used in the study.…”
Section: Solving;mentioning
confidence: 94%
“…First, this difference may be attributed to the special nature of scientific creativity. Scientific creativity is closely related to scientific knowledge (Hu, Adey, Shen & Lin, ; Okere, ). Therefore, promoting scientific creativity should be based on a certain amount of scientific knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Creative thinking in science subjects also appears to be influenced by gender. Okere and Ndeke (2012) identified considerable gender-related differences in scientific creativity in terms of flexibility, planning, and recognition of relations. Other researchers, however, have not found any significant gender-related differences regarding general creativity (Charyton & Snelbecker, 2007;Charyton et al, 2011).…”
Section: Gender In Creative Science Educationmentioning
confidence: 99%